Facet Joint Osteoarthritis Affects Spinal Segmental Motion in Degenerative Spondylolisthesis. Issue 8 (October 2018) - Kitanaka, Shigeyuki; Takatori, Ryota; Arai, Yuji; Nagae, Masateru; Tonomura, Hitoshi; Mikami, Yasuo; Inoue, Nozomu; Ogura, Taku; Fujiwara, Hiroyoshi; Kubo, Toshikazu
Abstract : Study Design: This is a retrospective clinical case series (case-control study). Objective: To clarify the influence of facet joint osteoarthritis (FJOA) on the pathology of degenerative spondylolisthesis (DS) using in vivo 3-dimensional image analysis. Summary of Background Data: There are no radical treatments to prevent progression of DS in patients with lumbar spinal canal stenosis associated with DS. Therefore, an effective treatment method based on the pathology of DS should be developed. Patients and Methods: In total, 50 patients with lumbar spinal canal stenosis involving L4/5 who underwent dynamic computed tomography were divided into 2 groups: with DS [spondylolisthesis (Sp) group; 12 male, 14 female; mean age, 74 y]; and without DS (non-Sp group; 15 male, 9 female; mean age, 70 y). Degeneration of the intervertebral disk and FJOA at L4/5 were evaluated using magnetic resonance imaging. Disk and intervertebral foramen heights, the distance between the craniocaudal edges of the facet joint, and the interspinous distance were measured on dynamic computed tomographic images. Also, in vivo 3-dimensional segmental motion was evaluated using the volume merge method. Results: There were no significant differences in degenerative findings for the intervertebral disk; however, progressive FJOA was detected in the Sp group. Dynamic changes in the distance between the craniocaudal edges of the facet joints were significantly larger in the Sp group. Conclusions: In this study, progressive FJOA and larger segmental motion in the distance between the craniocaudal edges of the facet joints were found in the Sp group. We clarified for the first time that DS involves ligament laxity due to FJOA that affects spinal segmental motion in vivo. We consider that a treatment method based on FJOA would be useful for treating patients with DS. Level of Evidence: Level IV.